SOFOSBUVIR FOR THE TREATMENT OF HEPATITIS C GENOTYPE 3 INFECTED PATIENTS IN PAKISTAN - Akhter, Tayyab Saeed; Umar, Muhammad; Khaar, Hammama-Tul-Bushra; Aslam, Faiza; Nisar, Gul; Naseer, Aqsa; Ahmad, Sadia; Osama, Muhammad (Journal of Ayub Medical College Abbottabad, 2017)
Background: This study was conducted to determine the viral responses of patients with chronic infection of Hepatitis C virus treated with sofubuvir. Methods: This Quasi experimental study was conducted at Centre for Liver and Digestive Diseases, Holy Family Hospital, Rawalpindi from September 2014 to September 2016. 502 patients with HCV genotype 3 including treatment naive, non-responders or relapsers to previous interferon based therapy along with patients having decompensated cirrhosis (child class B or C) were included in the study. All patients were treated with Sofosbuvir 400 mg once daily along with Ribavirin for 6 months. Follow-up qualitative PCR (polymerase Chain Reaction) were performed at 4 weeks interval to assess RVR (Rapid virological Response), end of treatment to determine ETR (End of treatment response) and 3 months post treatment to determine SVR12 (Sustained viral response at 12 week). Results: 91% of the patients had become PCR negative at completion of four weeks of treatment with Sofosbuvir, whereas at completion of treatment 96.5% had attained a negative PCR. Sustained virological response at 12 weeks post therapy (SVR12) was attained in 85.5% of patients. No statistically significant associations were found with attainment status of RVR, ETR and SVR based on previous treatment status or presence of Decompensated liver disease. However, attainment of SVR was slightly more in females (p value=0.03). The serological profiles of patients whether they attained PCR at week 4, 24 of treatment or 12 weeks’ post treatment did not exhibit any statistically significant difference. Conclusion: Sofosbuvir is effective in eradicating hepatitis C virus irrespective of previous treatment or liver fibrosis status in genotype 3 HCV Pakistani patients. Keywords: Sofosbuvir; Hepatitis C virus; infection; Polymerase chain reaction; virology; Genotype